The HITRAN2016 molecular spectroscopic database; Journal of Quantitative Spectroscopy and Radiative Transfer; Vol. 203 - Gordon I. E.; Rothman L. S.; Hill C.; Kochanov R. V.; Tan Y.; Bernath P. F.; Birk M.; Boudon V.; Campargue A.; Chance K. V.; Drouin B. J.; Flaud J. -M.; et al. (2017, 2017)
Title screen